Boosting Climate-Smart Potato Farming: Training of Trainers in Improved Practices for Smallholder Farmers with Disabilities in Rwanda - Barungi, Julian; Okonya, Joshua; Ilakut, Ben; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Over the years, Rwanda through its Rwanda Agriculture and Animal Resources Development Board has released several potato varieties with 10 new potato varieties released in 2023. Despite their good agronomic attributes that include high tuber yields, short maturity periods, tolerance to pest damage, resistance to common diseases such as late blight and potato viruses, very few smallholder youth and women farmers have adopted them. This is partly due to the high cost associated with purchase of quality declared or certified seed potato. Additionally, farmers especially youth and women have previously reported the limited technical knowledge in GAPs for production of certified and quality declared seed as one of the factors responsible for their low adoption of improved potato varieties and low yields. To address the challenge of low adoption rates and low yields, the training enhanced capacities of 75 participants (45 females, 30 males) in good agronomic practices in potato production and enhanced their access to improved potato varieties. The participants comprised women and youth farmer leaders, agro-input dealers, extension workers and seed potato store owners from Dukomeze Ubuzima Cooperative in Shingiro Musanze district of Rwanda. Through the support of the AICCRA project, ASARECA was able to hand over 2.5 tons of certified potato seed, 11 spray pumps, 200kgs of fertilizer, and assorted pesticides to 300 farmers belonging to the Dukomeze Ubuzima Cooperative, in Shingiro, Musanze, Rwanda as a starter pack for scaling the adoption of improved potato varieties.